2016
DOI: 10.5137/1019-5149.jtn.18702-16.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lumboperitoneal shunting in patients with normal pressure hydrocephalus

Abstract: ABSTRACTis one of the common effective treatment modalities used in the surgical management of communicating hydrocephalus, pseudotumor cerebri, CSF fistula and normal pressure hydrocephalus (NPH)(13).Its relative ease to perform and shorter surgery time, lack of risk for intracranial complications, including intracerebral hemorrhages, seizures or shunt dysfunction, lower risk of shunt infections and lethal complications all make LPS a favorable surgical treatment modality as compared to VPS surgery. Ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…24,26,29,43 Comparable results were reported for patients treated with VA 44,51 and LP shunts. 2,37,38 We found that cognitive function improved in more than 50% of patients who underwent shunting, with nonsignificant differences regarding the types of shunt used.…”
Section: Discussionmentioning
confidence: 76%
“…24,26,29,43 Comparable results were reported for patients treated with VA 44,51 and LP shunts. 2,37,38 We found that cognitive function improved in more than 50% of patients who underwent shunting, with nonsignificant differences regarding the types of shunt used.…”
Section: Discussionmentioning
confidence: 76%
“…LPS surgery is an effective surgical technique. It can be used as an alternative to the VPS procedure in the treatment of NPH patients (33).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the response rate varies among different studies depending on definition of improvement, treatment modalities, and follow-up duration [19,[50][51][52], previous reviews reported improvement in 71-83% of NPH patients [53,54]. In particular, gait disturbance is the most responsive sign of the NPH triad [55,56], and gait improvement following a CSF tap test or ELD is an important outcome predictor [54]. However, not all gait parameters respond to CSF diversion procedures and some NPH patients do not improve at all [57,58].…”
Section: Treatment Of Parkinsonism In Normal Pressure Hydrocephalusmentioning
confidence: 99%